Enhancing the teaching of linear structural analysis using additive manufacturing. (1st November 2017) - Virgin, Lawrence
Highlights: Innovative use of 3D printing. Frame stiffness. Sway approximations. Experimental testing. Abstract: Structural analysis forms a key component in many courses in civil, mechanical and aerospace engineering. Conventionally, the matrix stiffness method, a subset of finite element analysis, tends to occupy a central position in a typical syllabus, with a special focus on plane frames providing a bridge between basic structural components with pedagogical clarity and real-world structures. Equations of equilibrium are set-up and the full force of linear algebra brought to bear using the capabilities of Matlab or more specialized FEA packages. Such classes have a tendency to become a little dry and suffer from the usual shortcomings of numerical analysis and a black box approach - shortcomings in the sense of conceptual understanding as opposed to usefulness in the hands of experienced practitioners. The relatively recent advent of additive manufacturing is an exciting opportunity to incorporate a practical aspect to structural analysis. This paper describes the use of 3D printing, via the flexural stiffness of plane frames, to develop a structural feel for students, augmenting theoretical analyses. In addition to directly addressing the role of modeling, approximation, applicability of the underlying theory, and measurement uncertainty, it is thoroughly hands-on and initial anecdotal evidence suggests a higher degree of student buy-in.